Interactions of marine sulfated glycans with antithrombin and platelet factor 4 - Zhang, Wenjing; Jin, Weihua; Pomin, Vitor H.; Zhang, Fuming; Linhardt, Robert J. (Frontiers in Molecular Biosciences, 2022)
The molecular interactions of sulfated glycans, such as heparin, with antithrombin (AT) and platelet factor 4 (PF4) are essential for certain biological events such as anticoagulation and heparin induced thrombocytopenia (HIT). In this study, a library including 84 sulfated glycans (polymers and oligomers) extracted from marine algae along with several animal-originated polysaccharides were subjected to a structure-activity relationship (SAR) study regarding their specific molecular interactions with AT and PF4 using surface plasmon resonance. In this SAR study, multiple characteristics were considered including different algal species, different methods of extraction, molecular weight, monosaccharide composition, sulfate content and pattern and branching vs. linear chains. These factors were found to influence the binding affinity of the studied glycans with AT. Many polysaccharides showed stronger binding than the low molecular weight heparin (e.g., enoxaparin). Fourteen polysaccharides with strong AT-binding affinities were selected to further investigate their binding affinity with PF4. Eleven of these polysaccharides showed strong binding to PF4. It was observed that the types of monosaccharides, molecular weight and branching are not very essential particularly when these polysaccharides are oversulfated. The sulfation levels and sulfation patterns are, on the other hand, the primary contribution to strong AT and PF4 interaction.